Penggunaan Musik Sebagai Media Pembelajaran Anak Sekolah Dasar di Era Pandemi - Afnianthi Lutfiah Lumban Batu; Herawati Herawati; Ida Rosidah; Khalisa Salsabila; Sofia Isnaini Pinta; Yasmin Mutmainnah; Jennyta Caturiasari; Suko Pratomo (Universitas Pendidikan Indonesia Kampus Serang, 2021)
Remote learning (distance learning) is a program conducted by the government to minimize toleration and severed the link between the covid-19 virus dissemination. These long-distance learning are made by utilizing various digital technologies ranging from Zoom, Gmeet, Gmail, and WhatsApp. But in practice these long-range studies suggest there are some positive and negative facets. Teachers endeavor to utilize various technologies in the enjoyable learning process. Based on this, this community service aims to expose the use of songs as a learning medium for elementary school students besides that students can be stimulated to develop learning sharing through the lyrics of a song. By listening to songs that are designed or adapted besides related to the learning materials, students can indirectly listen to the learning materials. This method of community service program is also conducted through three stages of planning, implementation and evaluation. Studies have shown that songs can be used as interesting learning media besides that learning is more fun and can minimize lower motivations for elementary school children.